2009
DOI: 10.1007/s00125-009-1371-2
|View full text |Cite
|
Sign up to set email alerts
|

GAD65 vaccination: 5 years of follow-up in a randomised dose-escalating study in adult-onset autoimmune diabetes

Abstract: Because the study was initiated before 1 July 2005, the protocol was not registered in a registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 16 publications
1
59
0
Order By: Relevance
“…A dose-finding study in patients with latent autoimmune diabetes in adults (LADA) indicated that a prime and boost injection of 20 μg GAD-alum (recombinant human GAD 65 in a standard vaccine formulation with alum) might preserve residual insulin secretion [28]. This treatment was easy to perform and well tolerated by the patients, and at a follow-up after 5 years there were no treatment-related adverse events and potential efficacy was reported in one of the subgroups [29].…”
Section: Introductionmentioning
confidence: 97%
“…A dose-finding study in patients with latent autoimmune diabetes in adults (LADA) indicated that a prime and boost injection of 20 μg GAD-alum (recombinant human GAD 65 in a standard vaccine formulation with alum) might preserve residual insulin secretion [28]. This treatment was easy to perform and well tolerated by the patients, and at a follow-up after 5 years there were no treatment-related adverse events and potential efficacy was reported in one of the subgroups [29].…”
Section: Introductionmentioning
confidence: 97%
“…In NOD mice, administration of GAD 65 prevented type 1 diabetes and also protected transplanted islets after onset of the disease [11; 12]. A dose-finding study in Latent Autoimmune Diabetes in Adults (LADA) patients supported the clinical effect and safety of subcutaneous administration of 20 µg alum-formulated recombinant human GAD 65 (GADalum) [13], and the 5-year follow up suggests a persistent effect [14]. We have conducted a phase II clinical trial, where we showed that two injections of 20 µg GAD-alum contributes to the preservation of residual insulin secretion in children with recent onset type 1 diabetes [15].…”
Section: Introductionmentioning
confidence: 99%
“…While insulin autoimmunity is affecting the young, GAD65 autoimmunity is less sensitive to age. Alum-formulated recombinant human GAD65 tested in Phase II and III clinical trials were found to be safe [38][39][40] . The immunomodulating effect seemed to include the induction of Treg cells 16,38 and the residual beta-cell function in newly diagnosed T1D patients.…”
Section: Glutamic Acid Decarboxylase (Gad65)mentioning
confidence: 99%
“…GAD-alum tested in Phase II clinical trials with some effect on preserving residual cpeptide 39,40 was tested in an additional phase II trial with a dose-regiment that differed from previous trials 53 . Two or three doses of subcutaneous GAD-alum across 4-12 weeks did not alter the c-peptide disappearance rate during 12 month in newly diagnosed T1D patients (NCT00529399).…”
Section: Gad-alummentioning
confidence: 99%